THE APPLICATION OF PICTURES AND PEER ASSESSMENT FOR TEACHING DESCRIPTIVE TEXT IN WRITING CLASS - Komang Dian Puspita Candra (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2017)
English has four basic language skills those are listening, writing, reading and speaking. Teaching English at Junior high school is based on the school based curriculum. In competence based curriculum, students should be able to produce written texts based on certain genres, and one of them is descriptive text. Based on the observation, the ability of students in seventh grade of SMP Pemecutan Denpasar, in making descriptive text is lower than the other genres. Students feel bored in writing class and get stuck in describing something. Because of these difficulties, some efforts have been done to solve the problems. One of them is by teaching writing especially for descriptive text by using pictures and combined it with peer assessment. This study is intended to improve the ability of seventh grade students of SMP Pemecutan Denpasar in writing descriptive text. This study was designed in the form of classroom action research to 17 students that consists of two cycles and involving four steps in each cycle namely planning, action, observation and reflection. In order to collect the data, three instruments were used those are test, observation and questioner. The data were analyzed qualitative and quantitative based on rubric proposed by Brown (1994) and Nurgiyantoro (2010). The data analyses were presented in the table and chart as well as also in descriptive narrative sentences. The result of this study showed that the implementing of pictures and peer assessment could improve the ability of students in writing descriptive text. It can be seen from the mean score of students was 58 in pretest and after conducting the treatment in the first cycle the student’s mean score improved to 71 and become 77 in second cycle. There are 5 students (29,41%) who passed the KKM in pre test and there is a significant increasing in first cycle becomes 12 students (70,58%) and all students (100%) passed the KKM in second cycle. It can be inferred that the combination of pictures and peer assessment was very effective helping the students in writing a descriptive text and build their motivation in writing class.